Systematic Literature Review: Literasi Keuangan, Sikap Keuangan, dan Teknologi Keuangan terhadap Perilaku Keuangan Mahasiswa - Endarwati Endarwati; Mappa Panglima Banding; Mohamad Nur Utomo; Tinik Sugiati; Riskiyanto Riskiyanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to conduct a Systematic Literature Review (SLR) of research published in the last five years on financial literacy, financial attitudes, and the use of financial technology (fintech) and their influence on students’ financial behavior. Data were collected from the Scopus database, yielding 140 articles. After screening with the PRISMA diagram, 9 articles met the eligibility criteria and were analyzed further. The review shows that financial literacy serves as a crucial foundation for personal financial management, including saving, investing, and consumption. Positive financial attitudes encourage prudent financial behavior, while negative attitudes are often linked to risk avoidance and poor decision-making. The development of fintech, e-wallets, and mobile banking has expanded access to financial services, accelerated digital transactions, and strengthened daily financial practices. Digital financial literacy also plays a significant role, as strong digital skills foster caution in money management. Although most studies confirm the close relationship between literacy, attitudes, and financial behavior, gaps remain in exploring contextual factors such as culture, social media, and differences across academic disciplines and countries. Therefore, further research with broader scope and diverse methodologies is needed to comprehensively understand students’ financial behavior in the digital era.